Meningkatkan Kemampuan Menghitung Keliling Bangun Datar Melalui Media Geoboard bagi Anak Tunanetra - Selvina Putri Sundari; Mega Iswari (Ranah Research : Journal of Multidisciplinary Research and Development, 2022)
Background of this research was initially found when the writer led VII class at SLBN 1 Kota Padang Panjang special case happened to two male students AL and FR who unable to calculate circumference for two dimensional figures. In learning process, some tools could not encourage maximal result for class subject. By conducting this research, the writer purposed for describing geoboard which can improve calculation skill for circumference for dimensional figures that occur for two blind students. This research intended to focus on improving blind student skill for calculating circumference: rectangle, square and isosceles triangle. Furthermore, the writer used classroom action research. This method consisted two cycle, these are followed by some paths such as planning, conducting, observing, and reflection. Research sources are accomplished from students, teachers, also class grading when class is led for calculating circumference: rectangle, square and isosceles triangle that happened previous to post this research. At the beginning, AL achieved 10 score in class, however FR achieved 20. Applying cycle I, AL's score average increase to 30, FR's score 40. Thus, by using cycle II the writer found that processed reach better result when AL achieved 77,5 score, also happened for FR which average score is 82,5. At the end of analysis, the writer can conclude geoboard can improve blind student skill for calculating circumference in this case, dimensional figures.